A new species of Himacerus from South Africa (Hemiptera: Heteroptera: Nabidae) - Kerzhner, Izyaslav M.; Jacobs, Dawid H. (Zootaxa, 2008)
Himacerus frater sp. nov. is described from the western part of the Republic of South Africa. It is closely related to H. hottentotta (Reuter). A key to the Afrotropical species of Himacerus is given.